2009
DOI: 10.1177/0047287509336476
|View full text |Cite
|
Sign up to set email alerts
|

Walking in Memphis: Testing One DMO’s Marketing Strategy to Millennials

Abstract: This research examines the two promotional strategies most commonly used by destination marketers: traditional advertising and Web sites.While research concerning both advertising and the Internet is abundant, studies comparing tourism marketing strategies, especially those that target the Millennial generation, are limited. In this study a print advertisement and the official Web site for the Memphis Convention and Visitors Bureau are experimentally tested with a sample of members of the Millennial generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Due to the purchasing power and perceived influence that millennials hold in the market, it is imperative for destination marketers to develop strategies that help them to maximize their advertising efforts with optimal information sources (Loda et al , 2010). Characterized as being born “wired,” it has been suggested that millennials place a great importance on sharing information and connecting with their social networks (Gurtner and Soyez, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the purchasing power and perceived influence that millennials hold in the market, it is imperative for destination marketers to develop strategies that help them to maximize their advertising efforts with optimal information sources (Loda et al , 2010). Characterized as being born “wired,” it has been suggested that millennials place a great importance on sharing information and connecting with their social networks (Gurtner and Soyez, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Lee and Lockshin (2012) found that consumers’ perceptions of a country’s products influence their perceptions of the country as a travel destination. Loda, Coleman, and Backman (2010) found that consumers’ attitudes toward the advertisement and official website for a convention and visitors bureau have an impact on attitude toward the destination. More recently, Ryu, L’Espoir Decosta, and Andéhn (2016) showed that a positive evaluation of South Korean products could lead to a positive image of South Korea and even increase visit intention.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 98%
“…In particular, official destination websites are considered as an indispensable part of shaping the image of the destinations to an audience who may not be easily reachable via conventional channels (Govers & Go, 2003). These sites are found to be particularly more effective to engage with the Millennials than of printed advertisements (Loda, Coleman, & Backman, 2010). As a result, the effectiveness of the design of these websites is frequently scrutinised by scholars in hope of outlining users' preference on quality of information and ease of use of these virtual gateways to destinations (Kaplanidou & Vogt, 2006;Qi, Law, & Buhalis, 2008).…”
Section: Dmo Websites As the Focal Pointmentioning
confidence: 99%